STRATEGI PEMBELAJARAN AKIDAH AKHLAK DALAM MEMBENTUIK KARAKTER RELIGIUS PESERTA DIDIK DI MTS ALMAARIF O1 SINGOSARI - Maulidya Khilmawati; Dwi Fitri Wiyono; Qurroti A'yun (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The learning strategy of moral aqidah in the formation of religious character in the school of MTs AlMaarif 01 Singosari that is, can improve abilities and progres with the aim of increasing the abilities of students. And strives to form a generation that is faithful and devoted, has noble character, is skilled through public education, and religion. Researchers act as human instruments, this research uses a qualitative approach, with the type of case study research. In collecting the data, the researcher used data triangulation technique. The results of this study can be explained that planning learning strategies in shaping the character of students is using lesson plans and syllabus, preparing materials or teaching materials that will be discussed in. The implementation of learning strategies before the teaching and learning process begins with prayer, the teacher gives time to discuss, the aqidah moral teacher has an implementation process in shaping the religious character of students, namely by praying before starting learning, it can shape the religious character of students, namely by praying before starting learing, it can shape the religious character of student at MTs AlMaarif 01 Singosari. Submission of learning process in shaping strategies with discussion methods and lecture methods, moral aqidah teachers have a delivery process in shaping Â religious character in students by means of teaching and learning activities in the classroom through lessons, through inspiring stories to students, which when students conclude they cannot be separated, From the guidance of the moral creed teacher.Â Â